Exploring Students’ Mental Models of Photosynthesis: A Five-Tier Diagnostic Case Study in Senior High School - Alfyn Abdan Nurahman; Ari Widodo; Sariwulan Diana (Al Jahiz, 2026)
Understanding students’ mental models is essential to identify conceptual and representational challenges in learning intricate biological processes such as photosynthesis. This study explores senior high school students’ mental models of photosynthesis using a five-tier open-ended diagnostic test that integrates conceptual and visual understanding. A qualitative case study was conducted with 27 students in Bandung, Indonesia. The results revealed that only 22.8% of students demonstrated scientific understanding of the light reaction, and just 16.0% did so for the dark reaction. The majority of students exhibited initial or synthetic models, indicating fragmented knowledge, misconceptions, and difficulties in depicting key photosynthesis processes. Visualization results further highlighted students’ limited ability to construct accurate scientific representations, especially for the dark reaction. These findings suggest a need for model-based teaching strategies, multimodal representations, and formative assessments to enhance students’ conceptual and visual understanding of photosynthesis.